"I like the way I am, but I feel like I could get a little bit bigger": Perceptions of body image among adolescents and youth living with HIV in Durban, South Africa. - Patrick Nyamaruze; Kaymarlin Govender (PLoS ONE)
Body image concerns are common among people living with HIV (PLHIV). Research into how young people living with HIV (YPLHIV) experience and make sense of feared or actual body changes is limited, yet these changes have emotional, psychological and interpersonal implications for young people who associate physical attractiveness with social desirability. The current study examined the subjective perceptions of body appearance and coping mechanisms among a sample of YPLHIV in Durban, South Africa. An interpretive qualitative inquiry was adopted to understand their lived experiences in relation to their body image and body satisfaction. In-depth interviews were conducted with 18 YPLHIV (15-24 years). Findings indicate physical and psychosocial effects of living with HIV among young people including weight loss, skin sores, body dissatisfaction, loss of self-esteem and social withdrawal. The study builds on previous research suggesting that PLHIV may experience a discrepancy between their actual self and ideal self. Enhancing existing coping mechanisms such as religious beliefs, support networks and physical exercises among YPLHIV can counter the physical and psychosocial effects of living with HIV and improve well-being. Body image concerns should be acknowledged when addressing HIV-related health in both health and family settings.